2010
DOI: 10.1016/j.bpj.2010.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Dependent Nanomechanical Stability of Phase-Segregated Multicomponent Lipid Bilayers

Abstract: Cholesterol is involved in endocytosis, exocytosis, and the assembly of sphingolipid/cholesterol-enriched domains, as has been demonstrated in both model membranes and living cells. In this work, we explored the influence of different cholesterol levels (5-40 mol%) on the morphology and nanomechanical stability of phase-segregated lipid bilayers consisting of dioleoylphosphatidylcholine/sphingomyelin/cholesterol (DOPC/SM/Chol) by means of atomic force microscopy (AFM) imaging and force mapping. Breakthrough fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
85
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 71 publications
(131 reference statements)
18
85
1
1
Order By: Relevance
“…MSM/dioleylphosphatidylcholine (DOPC) at 25°C (i.e., below Tm of MSM [16]) or with that of other SM species in model bilayers [37][38][39][40]. The characterization of high-Tm lipid rich domains below 35°C is also in agreement with previous studies performed with dried Langmuir-Blodgett monolayers [8,9].…”
Section: Thermotropic Behavior and Identification Of Lipid Phasessupporting
confidence: 77%
See 2 more Smart Citations
“…MSM/dioleylphosphatidylcholine (DOPC) at 25°C (i.e., below Tm of MSM [16]) or with that of other SM species in model bilayers [37][38][39][40]. The characterization of high-Tm lipid rich domains below 35°C is also in agreement with previous studies performed with dried Langmuir-Blodgett monolayers [8,9].…”
Section: Thermotropic Behavior and Identification Of Lipid Phasessupporting
confidence: 77%
“…Previous reports have shown that this approach successfully scales high features of ordered lipid domains as significantly more rigid than the l d phase at ambient temperature [17,21,40,56]. To the authors' knowledge, except for the DPPC/cholesterol study by Redondo-Morata et al [42] no previous AFM investigation of the temperature-dependence of the mechanical properties had been reported so far on multiple-component lipid bilayers.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
See 1 more Smart Citation
“…This result can be observed in simulations (75). The rigidity of the platform should reduce such variations by increasing the elastic moduli of lipids and thereby suppressing bilayer geometry fluctuations (76)(77)(78)(79). The third potential source of noise for a channel comes from encounters with other proteins in the bilayer; this can be effectively reduced by the stiffened platform because not all membrane proteins are allowed in.…”
Section: Mechanical Roles Of Cholesterol-rich Platformmentioning
confidence: 88%
“…52,53,61 Scanning probe techniques such as AFM can be used to measure the thickness of SLBs [110][111][112] and the rigidity of pore spanning SLBs and to map the surface topography to, for example, visualize lipid rafts (Figure 1.7d). 96,113 The use of AFM in studying phase transitions in SLBs have recently been reviewed. 114 Combinations of QCM-D and AFM have been adopted to explore the intermediate states leading to SLB formation.…”
mentioning
confidence: 99%